2013
DOI: 10.1021/jp3093397
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrogen Bonding on Internal Conversion of GFP-like Chromophores. II. The meta-Amino Systems

Abstract: To rationalize the efficient quenching of the fluorescence and the Z → E photoisomerization of m-ABDI, the meta-amino analogue of the green fluorescent protein (GFP) chromophore, in protic solvents, the femtosecond time-resolved fluorescence and transient infrared (TRIR) spectra of m-ABDI in CD3CN, CH3OH, and CD3OD are determined. For solutions in CD3CN, the fluorescence decay lifetime is ∼7.9 ns and IR absorption lines near 1513, 1531, 1557, and 1613 cm(-1) of m-ABDI in its electronically excited state were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 59 publications
(123 reference statements)
5
53
1
Order By: Relevance
“…The results regarding to planar geometries are in good agreement with those reported in previous studies [20,35]. It can be seen, that the HOMO orbital has π-bonding and antibonding character on the γ and β bond, respectively.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The results regarding to planar geometries are in good agreement with those reported in previous studies [20,35]. It can be seen, that the HOMO orbital has π-bonding and antibonding character on the γ and β bond, respectively.…”
Section: Resultssupporting
confidence: 91%
“…Moreover, the probability of finding electrons at imidazolinone ring is negligible in the HOMO, but is significant in the LUMO. The enhanced charge-transfer character entails a reduction in S 1 →S 0 emission [20] which is supported by the short fluorescence lifetimes for all complexes [34]. From the HOMO delocalization we can infer that the enhanced charge transfer occurs during the deexcitation process and the extra electron density on phenol ring will attracts a proton since it is positively charged.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…[9][10][11] Their excited state fluorescence lifetimes (t f ) are also at least one order of magnitude higher than that of the para analogues. [9][10][11] Thus, enhancement of F f and t f could be achieved by structural modification. It has been shown that the extent of charge transfer is much higher for the meta analogues in comparison to the para analogues.…”
Section: Introductionmentioning
confidence: 95%
“…[1][2][3][4][5][6][7][8] This proposition has been extended to other unconstrained GFP chromophore analogues. [9][10][11][12] For example both p-HBDI and p-ABDI (Chart 1) have a Z-E isomerisation quantum yield (F ZE ) B 0.5 and F f B 0.0001. 9 However, meta analogues of these two molecules i.e.…”
Section: Introductionmentioning
confidence: 99%